PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION DI THE TRANS LUXURY HOTEL BANDUNG (Survei pada Wisatawan Sebagai Individual First Timer Guest The Trans Luxury Hotel Bandung) - Adytia, Cynthia Asrivionny; Yuniawati, Yeni (THE Journal : Tourism and Hospitality Essentials Journal, 2015)
Tourist’s needs of hotel are going higher contributes to the development of the hotel industry in Bandung. In 2013, the number of 5-star hotel has 9 hotels. Among the nine hotels is The Trans Luxury Hotel which opened in 2012 with a 6-star hotel concept. Despite its young age, The Trans Luxury has been able to attract people to stay so the occupancy rate has been able to achieve an average occupancy rate in the city of Bandung. In a period of 20 months, the number of guests who stayed at The Trans Luxury Hotel Bandung was dominated by individual guests, as many as 64%, while the number of business guests only reached 36%. Overall, the number of individual guests who stayed at The Trans Luxury Bandung during the period May 2012 to December 2013 was as much as 43.212 persons. The number of individual guests who stayed at The Trans Luxury Hotel Bandung is still dominated by first timer guests in the amount of 63.38%, so it can be identified that the guest’s intent to return still very low. As a new hotel, The Trans Luxury Hotel Bandung also has a goal to get the loyal customers. In the process of achieving customer loyalty, The Trans Luxury trying to focus on the characteristics of loyalty, one of them with efforts to increase guest’s intent in return to stay. In order to increase the guest’s intent in return to stay, The Trans Luxury Hotel Bandung implementing marketing strategies that focus on the individual guests, one of which is to implement customer experience. In this study, the independent variable (X) which is used is the customer experience includes the physical environment and social interaction. The dependent variable (Y) is revisit intention. This type of research is descriptive verification, and the method used was a survey with simple random sampling technique, and then obtained a total sample of 100 respondents. Techniques of data analysis and hypothesis testing used is a multiple linear regression analysis. The results showed that there is a strong relationship between customer experience with revisit intention which is equal to 0.658 and simultaneously the customer experience effect on revisit intention of 43.3%.